O processo coletivo e o IRDR ante a litigiosidade repetitiva e de massa - Jean, Olivier Haxkar (2020)
The evolution of rights has led to a new view of procedural codes, overcoming the privatist view of the individual right, to also protect group rights, which culminated in the elaboration of an advanced system of class action and collective protection of those rights. Despite this, the collective process was not enough to face the constant increase in litigation, in particular the mass tort cases. Seeking to face the growing increase of the litigation and the jurisprudence spread, the legislator, in the Code of Civil Procedure of 2015, brought a new procedural instrument called incident of resolution of repetitive demands (“IRDR”). The present dissertation aims to analyze and compare the main aspects of the two legal regimes, in order to extract a new vision of a broad and complementary regime that, associated with new artificial intelligence tools, can be capable of providing effective, fast and secure judicial protection